Impacts of the introduced European honeybee on Australian bee‐flower network properties in urban bushland remnants and residential gardens - Prendergast, Kit S.; Ollerton, Jeff (Austral ecology, 2022)
The European honeybee Apis mellifera is a highly successful, abundant species and has been introduced into habitats across the globe. As a supergeneralist species, the European honeybee has the potential to disrupt pollination networks, especially in Australia, whose flora and fauna have co‐evolved for millions of years. The role of honeybees in pollination networks in Australia has been little explored and has never been characterised in urban areas, which may favour this exotic species due to the proliferation of similarly exotic plant species which this hyper‐generalist can utilise, unlike many native bee taxa. Here, we use a bipartite network approach to compare the roles, in terms of species‐level properties, of honeybees with native bee taxa in bee‐flower (‘pollination’) networks in an urbanised biodiversity hotspot. We also assessed whether the abundance of honeybees influences overall network structure. Pollination networks were created from surveys across seven residential gardens and seven urban native vegetation remnants conducted monthly during the spring‐summer period over two years. There were consistent differences in species‐level properties between bee taxa, with honeybees often differing from all other native bees. Honeybees had significant impacts on network properties, being associated with higher nestedness, extinction slopes of plants, functional complementarity and niche overlap (year two), as well as lower weighted connectance and generalisation. These associations all are indicative that competition is occurring between the introduced honeybee and the native bee taxa in bee‐flower networks. In conclusion, the introduced honeybee occupies a dominant, distinct position in bee‐flower networks in urban habitats in the southwest Western Australian biodiversity hotspot and has a major, potentially disruptive, influence on plant‐pollinator network properties in these areas. The introduced European honeybee Apis mellifera was found to have significant impacts on bee‐flowering plant pollination networks in urban habitats, being associated with higher nestedness, extinction slopes of plants, functional complementarity, and niche overlap (year two), as well as lower weighted connectance and generalisation. There were consistently differences in species‐level properties between bee taxa, with honeybees often differing from all other native bees. These associations all are indicative that competition is occurring between the introduced honeybee and the native bee taxa in bee‐flower networks and indicate this species can have disruptive impacts on pollination networks.